Jalons historiographiques pour une histoire des prisons en Afrique francophone - Jean-Pierre Allinne (Clio@Themis)
The concept of prison is recurring in today’s african political literature. Its device of confinement of the men in a closed space goes up truly at the colonial period. The many punitive methods which had course in pre-colonial Africa privilegied more others forms of sanctions than the prison. This historiographic paper proposes to show the acquired kowledges ant the hypothesis which history of law must go deeply in the study of African colonial penitentiary system, our european law’s mirror.